Peningkatan Kapasitas SDM dalam Pengembangan Pemasaran di Era Digital untuk UMKM di Desa Air Batu Kota Palembang - Noviyanti, Iis; Asmalah, Lia; Hayati, Feb Amni (Jurnal PKM Manajemen Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting local economies, yet many still face challenges in marketing their products effectively, particularly in adapting to the digital era. In response to these challenges, a Community Service Program (PKM) entitled "Enhancing Human Resource Capacity in Digital Marketing Development for MSMEs in Air Batu Village, Palembang City" was conducted to increase local entrepreneurs’ digital marketing competencies. This PKM aimed to equip MSME actors with the necessary skills and knowledge to utilize digital platforms in promoting their products and expanding market reach. The activity was carried out in April 2025 in Air Batu Village, Palembang City, involving 15 lecturers from Universitas Pamulang as facilitators and 33 local participants. The implementation methods included a combination of material presentations, hands-on practice, group discussions, and interactive Q&A sessions. These methods were designed to be participatory and responsive to the specific needs of the participants. The results of the activity indicated a significant improvement in participants' understanding of digital marketing tools such as social media platforms, online marketplaces, and content creation. Participants expressed increased confidence in applying digital strategies to enhance their business visibility and customer engagement.